2016
DOI: 10.1002/2016jb013131
|View full text |Cite
|
Sign up to set email alerts
|

Passive rifting of thick lithosphere in the southern East African Rift: Evidence from mantle transition zone discontinuity topography

Abstract: To investigate the mechanisms for the initiation and early‐stage evolution of the nonvolcanic southernmost segments of the East African Rift System (EARS), we installed and operated 35 broadband seismic stations across the Malawi and Luangwa rift zones over a 2 year period from mid‐2012 to mid‐2014. Stacking of over 1900 high‐quality receiver functions provides the first regional‐scale image of the 410 and 660 km seismic discontinuities bounding the mantle transition zone (MTZ) within the vicinity of the rift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 63 publications
11
28
0
Order By: Relevance
“…Unlike differences observed in the Eastern Rift Branch, which might be attributed to anisotropy, these differences between the two studies are found in a region with a significant addition of new data from the Seismic Arrays for African Rift Initiation (Gao et al, ) and SEGMeNT arrays (Shillington et al, ). Therefore, we believe the differences observed in the our model give new evidence for thick lithosphere extending beneath the southern Malawi Rift is likely a result of improved resolution, and note the corroboration with recent potential field models (Sarafian et al, ) and transition zone receiver functions (Reed et al, ) suggesting the presence of the thick cratonic lithosphere in these regions.…”
Section: Discussionsupporting
confidence: 86%
“…Unlike differences observed in the Eastern Rift Branch, which might be attributed to anisotropy, these differences between the two studies are found in a region with a significant addition of new data from the Seismic Arrays for African Rift Initiation (Gao et al, ) and SEGMeNT arrays (Shillington et al, ). Therefore, we believe the differences observed in the our model give new evidence for thick lithosphere extending beneath the southern Malawi Rift is likely a result of improved resolution, and note the corroboration with recent potential field models (Sarafian et al, ) and transition zone receiver functions (Reed et al, ) suggesting the presence of the thick cratonic lithosphere in these regions.…”
Section: Discussionsupporting
confidence: 86%
“…However, a lack of such upwelling in the rest of the Eastern Branch and the entire Western Branch makes such a rifting mechanism unlikely for the Eastern and Western Branches. The absence of significant thermal upwelling from the lower mantle beneath other segments of the EARS has also been inferred for the Afar Depression (Reed, Gao, et al, ), the Malawi Rift of the EARS (Reed, Liu, et al, ), and the Okavango Rift (Yu, Liu, et al, ) and is suggested by geodynamic modeling (Quere & Forte, ; Stamps et al, ; ).…”
Section: Discussionmentioning
confidence: 68%
“…We propose that this thick lithosphere represents the NE continuation of the Niassa Craton—a little cratonic block in eastern Zambia and that has been identified using magnetotelluric imaging (Sarafian et al, ). In addition, Reed et al () found an apparent 20‐km shallowing of the mantle transition zone that they attribute to high‐velocity anomalies in the upper mantle. This result from Reed et al () also supports the existence of relatively thick and strong lithosphere in the south‐central MR.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have been conducted to investigate the crustal and upper mantle structures beneath the MR using controlled-source seismic (lake-bottom seismometers), body and surface wave tomography, and receiver function stacking (Accardo et al, 2017;O'Donnell et al, 2013;Reed et al, 2016). O'Donnell et al (2013) used Rayleigh wave phase velocity to invert for a 3-D shear wave velocity model and observed pronounced velocity lows beneath the northern and southern ends of the Lake Malawi but not beneath the central portion of the lake.…”
Section: Previous Geophysical Studies Of the Mrmentioning
confidence: 99%
See 1 more Smart Citation